Caracterização das formas juvenis e adultas dos camarões-rosa Farfantepenaeus brasiliensis (Latrelle, 1917) e F. paulensis (Perez-Farfante, 1967) (Decapoda: Penaeidae) por meio de técnicas moleculares e morfologia comparativa - Teodoro, Sarah de Souza Alves [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The greatest difficulty in identifying the pink shrimps Farfantepenaeus brasiliensis and F. paulensis occurs mainly in the juvenile stage, when secondary sexual characters are still in formation and the only way to separate them is by observing the dorsal furrow of the sixth somite. In this way, the present study aimed to verify the identity of F. brasiliensis and F. paulensis, using molecular and morphometric techniques. Additionally, it was also compared the population stocks of these species at three different regions along the coast of the Southeastern region, at São Paulo State. Extraction of genomic DNA, amplification of the COI gene (also used for DNA Barcoding system ), purification and sequencing were performed . The analyzes (haplotype network , analysis of genetic distance and dendrogram ) showed no genetic variability among the population stocks. F. brasiliensis and F. paulensis are valid species, the COI gene is efficient to separate such species, there is no genetic variation among the sampled sites for both species and the traditional characters do not allow the correct identification of both species juveniles. Considering only the molecular identity of the species, all variables measured for the traditional morphometry were significant in separating the groups analyzed. The discriminant analysis showed significant differences between the two species studied (p < 0.05). The geometric morphometric analysis of the carapace shape of individuals of F. brasiliensis and F. paulensis resulted in 16 relative warps and 2 uniform components. There were no differences in the shape of the carapace between the two species analyzed, both for males and females. Contrary to the expected, the structures identified by morphometric (traditional and geometrics) as significantly different among individuals were very subjective and they were not reliable for the identification of F. brasiliensis and F. paulensis. However, when analyzing the ...

A dificuldade maior na identificação dos camarões-rosa Farfantepenaeus brasiliensis e F. paulensis ocorre principalmente na fase juvenil, quando os caracteres sexuais secundários ainda encontram-se em formação e o único modo de discerni-las é por meio da observação do sulco dorsal do sexto somito. Assim, para o presente estudo propôs-se verificar, por meio de técnicas moleculares e morfométricas, a identidade de F. brasiliensis e F. paulensis. Adicionalmente, foram comparados os estoques populacionais das espécies em questão em três diferentes localidades ao longo da costa da região Sudeste, no estado de São Paulo. Foi realizada a extração do DNA genômico, amplificação do gene COI (usado também para o sistema de DNA Barcoding), purificação e sequenciamento. As análises realizadas (rede de haplótipos, análise de distância genética e pelo dendrograma) não mostraram variabilidade genética entre os estoques populacionais. F. brasiliensis e F. paulensis são espécies válidas; o gene COI é eficiente para separar tais espécies; não há variação genética entre as localidades amostradas para as duas espécies e os caracteres tradicionais não permitem a correta identificação dos juvenis das duas espécies. Considerando somente a identidade molecular da espécie, todas as variáveis mensuradas para a morfometria tradicional foram significativas na separação dos grupos analisados. A análise de discriminante demonstrou diferenças estatísticas entre as duas espécies estudadas (p<0,05). As análises de morfometria geométrica na forma da carapaça dos indivíduos de F. brasiliensis e F. paulensis resultaram em 16 relative warps e 2 componentes uniformes. Não foram encontradas diferenças visíveis na forma da carapaça entre as duas espécies analisadas, tanto para machos quanto para fêmeas. Ao contrário do esperado, as estruturas apontadas pelas morfometrias (tradicional e geométrica) como ...
Keywords: Camarão - Identificação; Decapode (Crustaceo); Morfometria; Biometria; Genetica molecular; Decapoda (Crustacea)